Diseminasi Hasil Penelitian Partisipasi Anggaran sebagai Strategi Reduksi Ketimpangan Wilayah Papua Selatan - Irianto, Okto; Ferry Sutiono; Lutfi Nasrullah (Insan Kreasi Media, 2025)
South Papua Province, as the youngest province in Indonesia, receives significant Special Autonomy funds of IDR 790 billion annually. However, regional inequality remains a critical challenge with a Williamson Index of 0.42 (high category). Previous research identified that ineffective budget utilization stems from low budgetary participation, which significantly affects managerial performance (β = 0.462; R² = 66.2%). This community service aimed to disseminate research findings on budgetary participation as a key to managerial performance and regional inequality reduction strategy to structural officials managing Special Autonomy funds. The activity employed a Community-Based Education approach combined with Research Dissemination and Knowledge Transfer strategy, involving 25 participants from various Regional Government Agencies in Merauke Regency on December 15, 2024. The dissemination included four interactive sessions: research findings presentation, group discussions with case studies, strategic recommendations, and commitment building. Evaluation results demonstrated exceptional achievement, with an average satisfaction score of 4.33 out of 5 (exceeding the 4.0 target) and 84.7% of participants committed to implementing participatory budgeting principles (exceeding the 70% target). This activity serves as a catalyst for fundamental transformation of the budgeting system from top-down to participatory model, contributing to regional inequality reduction through improved managerial performance and effective development program execution in South Papua.